2009
DOI: 10.1097/aap.0b013e3181add8a3
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Ultrasound Imaging, Cross-Sectional Anatomy, and Histology of the Brachial Plexus

Abstract: The anatomy of the brachial plexus is complex. To facilitate the understanding of the ultrasound appearance of the brachial plexus, we present a review of important anatomic considerations. A detailed correlation of reconstructed, cross-sectional gross anatomy and histology with ultrasound sonoanatomy is provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(52 citation statements)
references
References 43 publications
1
51
0
Order By: Relevance
“…1,2 This may be due to the limitation of conventional ultrasound to distinguish muscle fascia from epineurium and small fascicles, [3][4][5] such that mechanical nerve injury, barotrauma, or local anesthetic toxicity may result from unintended injection into critical nerve structures. 1,[6][7][8][9][10] This has recently led investigators to focus on how best to avoid nerves while still achieving a reliable block.…”
Section: Résumémentioning
confidence: 99%
“…1,2 This may be due to the limitation of conventional ultrasound to distinguish muscle fascia from epineurium and small fascicles, [3][4][5] such that mechanical nerve injury, barotrauma, or local anesthetic toxicity may result from unintended injection into critical nerve structures. 1,[6][7][8][9][10] This has recently led investigators to focus on how best to avoid nerves while still achieving a reliable block.…”
Section: Résumémentioning
confidence: 99%
“…16 Although these results suggest that PNS-or paresthesia-guided needles are likely placed within nerves much more frequently than previously realized, and that the usual absence of injury is likely explainable by the relative ease of placing needles into connective tissue rather than into a fascicle, in vitro studies of human sciatic nerve nevertheless demonstrate that sharp needles, in fact, enter fascicles 3.2% of the time, thereby potentially causing injury. 17 Moreover, as one proceeds proximal to distal, the amount of nonneural connective tissues present within the cross-sectional area of the brachial plexus increases, 18 suggesting that the interscalene area may be less forgiving of subepineurium needle placement compared with the axillary or supraclavicular areas. Thus, US is a more sensitive indicator of needle-to-nerve contact than either paresthesia or PNS, but it is unknown if this advantage translates to actual reduction of nerve injury.…”
Section: Peripheral Nerve Injurymentioning
confidence: 99%
“…However, even at proximal brachial plexus block sites, the majority of the intraneural space typically consists of connective tissue. A correlative ultrasound imaging study has been performed reporting the ultrasound appearance of the brachial plexus at common regional block sites with cross-sectional gross anatomy and .............................................................................................................................................................................................................. [4]. This study also documented increasing amounts of connective tissue in the distal brachial plexus and suggested that the typical increased hyperechoic appearance of the distal brachial plexus on ultrasound correlated with the increase in connective tissue.…”
Section: ó 2011 the Authorsmentioning
confidence: 99%
“…Direct nerve trauma may be particularly important during proximal brachial plexus block as these blocks have the highest incidence (1-6%) of neurological complications [2]. Anatomical studies have noted that the amount of non-neural tissue around the brachial plexus is least at proximal sites (such as the interscalene area) and increases distally (axillary) [3,4]. Thus, there may be a smaller margin for error for extraneural placement of needles and local anaesthetic solution at proximal sites and precise targeting of block needles may be advantageous.…”
mentioning
confidence: 99%